Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5937/ekopolj1904055a
|View full text |Cite
|
Sign up to set email alerts
|

A review of wine and wine tourism presence in the scientific papers in journals in the field of tourism

Abstract: The aim of this paper is to indicate the representation of the papers related to wine and wine (eno) tourism in the scientific journals in the field of tourism from the Journal Citation Reports (JCR) list, with the Impact Factor (IF)-Clarivate Analytics. Fifteen journals have been analyzed on the basis of the phrase presence related to wine and wine tourism in titles, keywords and abstracts. 91 papers have been singled out, with their review per journal, as well as summary of publication frequency per year. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…For example, wine tourism is increasingly relevant not only in practice but also in scientific research. This is confirmed by the research by Anđelić et al (2019), where is concluded that in journals which names refer directly to the tourism/tourist (from Journal Citation Report -JCR with Impact Factor -IF) the greatest number of papers about wine and wine tourism was published in the 21 st century (94.51%), especially in its second decade (57.14%) (p. 1081).…”
Section: Introductionmentioning
confidence: 60%
“…For example, wine tourism is increasingly relevant not only in practice but also in scientific research. This is confirmed by the research by Anđelić et al (2019), where is concluded that in journals which names refer directly to the tourism/tourist (from Journal Citation Report -JCR with Impact Factor -IF) the greatest number of papers about wine and wine tourism was published in the 21 st century (94.51%), especially in its second decade (57.14%) (p. 1081).…”
Section: Introductionmentioning
confidence: 60%
“…Naturally, people contribute to more complete usage of some natural potentials, so the benefits are used for the development of various types of tourism. For example wine tourism, which is extensively researched in the scientific and professional literature (Anđelić et al, 2019), organic production, as well as rural tourism, and closely observed agritourism as an addition to the existing types of contacts with clients and agricultural product distribution already discussed by Milanovic et al (2019) and Milanović et al (2020).…”
Section: Introductionmentioning
confidence: 94%
“…The earliest evidence of grape wine has been found in China (around 7000 BC), Georgia (around 6000 BC), Iran (around 5000 BC), Greece (around 4500 BC), and Sicily (around 4000 BC) (McIntyre & Gremov, 2018). Today, it is almost unthinkable to organize any event, be it festivities, entertainment, various life events, culinary concepts, or touristic trips without wine (Anđelić et al, 2019). Wine has begun to take up a more substantial role in many countries' tourism offerings, creating a distinct tourism product (Razović, 2015).…”
Section: The Role and Importance Of Wine And Digital Wine Listsmentioning
confidence: 99%